AP GP HP Cheatsheet

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

Arithmetic Progression Properties of GP : 1

general term : an =
General term : an = a + (n − 1)d 1
+ (n − 1)d
nth term from end : a + (m − n)d • GP divided/multiplied by constant, stays GP a1
where nth term from end = (m − n + 1) from start Harmonic Mean(H)
• reciprocal of GP, is GP
if A,B,C are in AP: 2B = A + C • a1 an = a2 an−1 = ak an−k+1 2ab
• H=
a+b
a1 + an = a2 + an−1 • b2 = ac
• a, H1 , H2 . . . , Hn , b are in HP
2an = an+k + an−k
• for a GP a1 , a2 . . . an
1 1 1 1 1 1
selecting middle term of AP: ⇒ GM = (a1 a2 . . . an ) n then , , ..., , are in AP
a H1 H2 Hn b
ODD ⇒ −a+ CD → d 1
EVEN ⇒ (a − d)(a + d) CD → 2d • if a1 , a2 . . . an ⇒ GP → = (n + 2)th
log a1 , log a2 . . . log an ⇒ AP and vice-versa b
1 1 a−b
Sum of AP :
results of sum of GP : → = + (n + 1)D D=
n b a (n + 1)ab
with common difference Sn = {2a + (n − 1)d}
2   n

a 1 − r , r 6= 1 Arithmetico-geometric Sequence
n Sn = 1−r a, (a + d)r, (a + 2d)r2 , . . . is a A.G. sequence
with last term Sn = {a + l}
2 na, r

results of sum of AP : nth term : an = {a + (n − 1)d}.rn−1


a − lr lr − a
• Seq is AP → if sum of n terms form An2 + Bn Sn = 1 − r = r − 1 a d.r
sum of ∞ term : S∞ = +
• if ratio of sum is given, then ratio of n th
term 1 − r (1 − r)2
n a
is S∞ = −1 < r < 1
→ replace n by 2n − 1 1−r
Sum of Some Sequence
th
• if ratio of n term is given, then ratio of sum
Harmonic Progression n(n + 1)
is first n natural no :
n+1 if a1 , a2 . . . an are in HP 2
→ replace n by
2
1 1 1 n(n + 1)(2n + 1)
then , ... are in AP square of first n no :
a1 a2 an 6
Geometric Progression
General terms : an = arr−1
n(n + 1) 2
 
nth term from end : an = arm−n 1 1 cube of first n no :
 n−1 common difference : d= − 2
1 a2 a1
using last term : an = l
r n(n + 1)(2n + 1)(3n2 + 3n − 1)
4th power of n no :
30

Prashant Dhirendra : prashant.dhiru@gmail.com


Relation between AM, GM and HM Tips and Tricks
(black space tips,tricks and important question)
• A,G and H between 2 numbers(a and b):

a+b √ 2ab
A= G= AB H=
2 a+b

• A>G>H

• quadratic eq having a and b as its roots

x2 − 2Ax + G2 = 0
p
• the two numbers(a,b) are A ± A2 − G2

• if A and G are in the ratio m : n, then the


number(a,b) are in ratio
p p
m + m2 − n2 : m − m2 − n2

• A,G and H between 3 numbers(a, b, c):


 
a+b+c 1 1 1 1 1 1
A= G = (abc) 3 = + +
3 H 3 a b c

• cubic equation where a,b,c are the roots

3G3
x3 − 3Ax2 + x − G3 = 0
H

Prashant Dhirendra : prashant.dhiru@gmail.com

You might also like